The Mediating Effect of Human Capital on the Relationship Between Strategic Innovation and the Performance of Manufacturing SMEs in Yemen - AlQershi, Nagwan; Abas, Zakaria Bin; Mokhtar, Sany Sanuri Mohd (Organizations and Markets in Emerging Economies, 2019)
The purpose of this paper is to fill gaps in the human capital literature, first, by providing insights into the relationship between human capital and strategic innovation and the performance of Small and Medium Enterprises (SMEs), and second, by exploring the role of human capital as a mediating variable. Although SMEs perform a vital role in the economic development of countries worldwide, developing countries tend to lag behind developed countries in this sector; hence, there is a need to investigate the peculiar nature of SMEs and their performance in the context of developing countries. Additionally, understanding an organization’s human capital requires the articulation of a system of variables that helps to uncover and manage the visible wealth. The contribution of SMEs can be measured through performance. This study is a conceptual discussion of manufacturing SME performance in Yemen and the effect of human capital and strategic innovation. The performance is considered to be very low, and the country is ranked by the Global Innovation Index as one of the lowest in terms of innovation. This paper describes the development of a framework which is a clear manifestation of the knowledge gap addressed by this study.